Analysis of Shipyard to Meet Fish Ship Procurement Plan for The Ministry of Marine and Fisheries - Agus Lubis Fitriansyah; Heri Supomo (Jurnal Sains dan Seni ITS, 2019)
To Improve the national fishing vessels and the welfare of fishermen, the government will provide fishing vessels grant through the KKP. The current capacity of fiberglass shipyards is unclear,so the realization of the procurement of fishing vessels is not accordance with the planned targets. This study aims to analyze shipyard capacity to support the plan for the procurement of KKP fishing vessels grant in 2019. First classify fishing vessels based on their respective GT sizes, which are <5 GT (type A), 5-10 GT (type B), and 20-30 GT (type C). Second, make the minimum shipyard criteria in building fishing vessels. Third, count the number of ships that can be built by the shipyard. The results of the shipyard analysis of the minimum criteria found that 43% of shipyards have the ability to build type A vessels, about 38% of shipyards have the ability to build type B vessels, and around 19% of shipyards have the ability to build type C vessels. which can be built is 1625 units / period. Referring to shipyard capacity, it can be said that the entire shipyard is able to fulfill the plan to procure assistance for KKP fishing vessels in the 2019 budget year.